Case-control study on regular Ba Duan Jin practice for patients with chronic neck pain - Jing-Yuan Wang; Hong Guo; Ling Tang; Jing Meng; Li-yun Hu (Elsevier, 2014)
Purpose: To observe the long-term effects of regular Ba Duan Jin exercises for patients with chronic neck pain. Methods: Participants with chronic neck pain were instructed to perform ≥30 min/d of Ba Duan Jin exercises (n = 36) or assigned to a control group (n = 36) for six months. Data from a visual analogue scale, Northwick Park Neck Pain Questionnaire, and the 36-item Short-form Health Survey (SF-36) were collected before, and three and six months after intervention began. Results: Participants undergoing Ba Duan Jin exercises achieved significantly greater improvement than the controls in visual analogue scale, Northwick Park Neck Pain Questionnaire and SF-36 health transition scores (all p < 0.05). However, no significant differences were observed in SF-36 physical or mental component summaries. Conclusion: Regular Ba Duan Jin practice reduces suffering and pain, and increases health satisfaction in individuals with chronic neck pain.